The impact of dosing schedules on the success of vaccination programmes in elderly populations: A summary of current evidence. Issue 8 (3rd August 2018) - Matthews, Ian; Dawson, Hazel
ABSTRACT: Vaccines are an established means of preventing and eliminating communicable diseases. Whilst their efficacy in some settings is well studied, the impact of multi-dose vaccinations programmes in elderly populations is not well documented. A literature review was conducted in order to collate and analyse existing publications to provide a summary of current thinking and support identification of key factors that impact on the success of vaccination programmes. Having returned little information to provide a comprehensive understanding of the subject area, two short surveys were undertaken to supplement the findings and further examine the attitudes and opinions of the elderly and healthcare professionals. Combining the results from all three research methodologies suggests that vaccination programmes with fewer doses are associated with improved course completion rates and a lower logistical and economic burden. Whilst it is acknowledged that this study has limitations, it provides relevant insights in a space where there is little research to inform the work programmes of vaccines in development and support optimisation of ongoing programmes. It also highlights the need for further research to fully understand the factors influencing successful vaccination programmes in this specific patient population.